Penilaian Simpang Tak Bersinyal Bundaran Jalan Duyung dan Jalan Raja Ali Haji Kota Batam Menggunakan Manual Kapasitas Jalan Indonesia (MKJI) - Willy Anthony; Jody Martin Ginting; Petrus Haryanto Wibowo (Faculty of Engineering, Kadiri University, 2022)
Good transportation system can encourage economic growth and support development. Therefore, the success of development in the economic sector must be supported by the development of a good transportation system, because a bad transportation system can cause a slow pace of the economy of a region. One of the transportation problems that often occurs is congestion. Batam City currently has a high rate of increase in motorized vehicles making it possible for congestion to occur. The purpose of this study was to assess the traffic performance of unsignalized intersections on Jalan Duyung and Jalan Raja Ali Haji Batam City. The reference used in this research is MKJI 1997. The research was conducted by conducting a traffic survey to obtain traffic data and road geometry. Furthermore, capacity analysis and traffic behavior are carried out. The result of this research is a capacity of 2422 pcu/hour and Qtotal of 1966 pcu/hour so that the obtained DS is 0.812 which means more than 0.75, so it can be said that this intersection is slightly ineffective. At the intersection traffic delay, the value is 9.3, DTMA is 6.8, DTMI is 23.4 pcu/hour, DG is 4.072 sec/pcu, D is 13,372 sec/pcu, and the queue probability is 26% - 50% where This queue probability slightly exceeds the standard limit of 23% - 45% so that this intersection has a slightly high level of traffic queue probability. The results obtained from this study can be used as a reference for improving the performance of unsignalized intersection traffic.